Optimum Extraction Condition of Clitorea ternatea Flower on Antioxidant Activities, Total Phenolic, Total Flavonoid and Total Anthocyanin Contents - Nurjamalina Fasihah Jaafar; Muhammad Ezzudin Ramli; Rabeta Mohd Salleh (Tropical Life Sciences Research, 2020)
Clitoria ternatea is a herbaceous plant with many health benefits. Extraction is crucial to obtain its bioactive components which contribute to its antioxidant properties. Therefore, this study was conducted to find an optimum extraction condition of C. ternatea flower on total phenolic content (TPC) and antioxidant activity (2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical-scavenging activity) as well as to determine its total flavonoid content (TFC) and anthocyanin content based on the optimum extraction condition generated by Response Surface Methodology (RSM)-Design Expert 7.1.5. TPC, TFC and total anthocyanin of C. ternatea were conducted by Folin Ciocalteu (FC), calorimetric assay and pH differential method, respectively. The ranges of selected independent variables were ethanol concentration (30ºC–90% v/v), time (60–120 min) and temperature (30ºC–70ºC). The optimum extraction condition was obtained at 39.62% v/v ethanol concentration, 90 min and 44.24ºC. However, these values were slightly adjusted according to the convenience of equipment to operate in which ethanol concentration was adjusted to 37% v/v, time remain at 90 min and temperature at 45ºC. The predicted values of TPC and DPPH radical scavenging activity were 41.60 mg GAE/g dry samples and 68.12% inhibition and were experimentally verified to be 41.17 ± 0.5 mg GAE/g dry samples and 63.53 ± 0.95% inhibition of TPC and DPPH radical scavenging activity respectively. This result has showed RSM can optimise TPC and radical scavenging activity of C. ternatea. Upon the optimum condition, the TFC determined was 187.05 ± 3.18 mg quercetin/g dried sample which was higher than TPC and the total anthocyanin content was 28.60 ± 0.04 mg/L. Hence, the extractable phenolic, flavonoid and anthocyanin compounds indicated that C. ternatea is a good source of natural antioxidant. Clitoria ternatea adalah tumbuhan herba yang banyak kebaikan kesihatan. Pengekstrakan adalah penting untuk mendapatkan komponen bioaktif yang menyumbang kepada sifat antioksidannya. Oleh itu, kajian ini dijalankan untuk mendapatkan keadaan pengekstrakan yang optimum ke atas bunga C. ternatea terhadap jumlah kandungan fenolik (TPC) dan aktiviti antioksidan (2,2-difenil-1-picrylhydrazyl (DPPH) aktiviti pemerangkapan radikal bebas) serta menentukan jumlah kandungan flavonoid (TFC) dan antosianin berdasarkan keadaan pengekstrakan optimum yang dihasilkan oleh Metodologi Respons Permukaan (RSM)-Design Expert 7.1.5. TPC, TFC dan jumlah antosianin C. ternatea masing-masing ditentukan oleh Folin Ciocalteu (FC), ujian kalorimetri dan kaedah pembezaan pH. Pembolehubah bebas yang dipilih adalah kepekatan ethanol (30%–90% v/v), masa (60–120 min) dan suhu (30ºC–70ºC). Kondisi pengekstrakan optimum diperolehi pada kepekatan ethanol 39.62% v/v, 90 min dan 44.24ºC. Walau bagaimanapun, nilai-nilai ini telah diselaraskan mengikut kemudahan peralatan untuk beroperasi iaitu ethanol diselaraskan kepada 37% v/v, masa kekal pada 90 min dan suhu pada 45ºC. Nilai ramalan kandungan fenolik dan aktiviti pemerangkapan radikal DPPH adalah 41.60 mg GAE/g sampel kering dan 68.12% perencatan radikal dan experimen pengesahan keadaan optimum mendapati keputusan TPC ialah 41.17 ± 0.5 mg GAE/g sampel kering dan keputusan pemerangkapan radikal DPPH ialah 63.53 ± 0.95%. Keputusan ini menunjukkan bahawa RSM dapat mengoptimumkan pengekstrakan TPC dan aktiviti antioksidan C. ternatea. Berdasarkan keadaan pengektrakan yang optimum, jumlah kandungan flavonoid yang ditentukan ialah 187.05 ± 3.18 mg quercetin/g sampel kering yang iaitu lebih tinggi daripada kandungan TPC dan jumlah kandungan antocianin adalah 28.60 ± 0.04 mg/L. Oleh itu, komponen fenolik, flavonoid dan antosianin yang boleh diekstrak menunjukkan bahawa C. adalah sumber antioksidan semula jadi yang baik.